Wybrane czynniki kształtujące ceny detaliczne mięsa oraz przetworów wieprzowych i drobiowych - Olszańska, Anna (Chosen Factors Forming Retail Prices of Meat and Pigs and Poultry Products, 2006)
The aim of the paper is an initial analysis of retail prices of meat products in Poland between 1995 and 2005 and relations between those prices (containing relations between prices of pigs and poultry for slaughter and meat products) and estimating how the companies form the prices in connection with competitive products on the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 179-187